Methodological aspects of the development of the future choirmasters’ emotional competence - Tkachenko Maryna (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2021)
The article reveals the essence and features related to the development of the future choirmasters’ emotional competence in the process of profession-oriented training. The purpose of the article is to determine the methodological approaches and pedagogical principles of forming the emotional competence of future choirmasters in the process of profession-oriented training. The competence-based paradigm of art-centred education is defined as the one that is aimed at gaining the experience necessary for making constructive decisions in a nonlinear, variable and unpredictable process of performing and art-pedagogical practice. Emotional competence is interpreted as an integral quality, a set of knowledge, skills, abilities and practical experience of the conscious handling of emotional information and volitional regulation of emotional behaviour in the process of working with the choir aimed at optimizing the emotional aspect of artistic communication through reflexivity, empathy and appropriate conducting expression. The component structure of the future choirmasters’ emotional competence has been determined; it includes person-oriented cognitive, analytical-interpretive, sensory-expressive and reflexive-regulatory components. The theoretical and methodological basis for the development of the future choirmasters’ emotional competence is considered. The acmeological approach is aimed at the maximum disclosure of the student’s internal potentials, which is possible through designing individual performing and pedagogical trajectory. The hermeneutic approach helps to master new knowledge related to one's own inner world, emotional manifestations of other knowledge and artistic emotions that are transmitted in the musical text. The reflexive approach enables a substantive vision of the emotional component of profession-related activities as a result of productive introspection. The pedagogical principles facilitating the development of the future choirmasters’ emotional competence have been distinguished: the principle of subjective activity, the principle of emotional dominance and the principle of systematization of emotional experience.